2009
DOI: 10.1016/j.molcel.2009.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Rtr1 Is a CTD Phosphatase that Regulates RNA Polymerase II during the Transition from Serine 5 to Serine 2 Phosphorylation

Abstract: SUMMARY Messenger RNA processing is coupled to RNA Polymerase II (RNAPII) transcription through coordinated recruitment of accessory proteins to the Rpb1 C-terminal domain (CTD). Dynamic changes in CTD phosphorylation during transcription elongation are responsible for their recruitment, with serine 5 phosphorylation (S5-P) occurring towards the 5’ end of genes and serine 2 phosphorylation (S2-P) occurring towards the 3’ end. The proteins responsible for regulation of the transition state between S5-P and S2-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
171
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(189 citation statements)
references
References 47 publications
18
171
0
Order By: Relevance
“…2D). These results are consistent with the observation that RTR1 deletion increases CTD serine 5 phosphorylation throughout the gene (47), whereas SSU72 appears to act during termination (28).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2D). These results are consistent with the observation that RTR1 deletion increases CTD serine 5 phosphorylation throughout the gene (47), whereas SSU72 appears to act during termination (28).…”
Section: Resultssupporting
confidence: 92%
“…To test whether the 6AU sensitivity of set1⌬ strains could be related to excessive CTD phosphorylation, the two known CTD serine 5 phosphatases Rtr1 (47) and Ssu72 (48,49) were overexpressed from galactose-inducible promoters. Overexpression of Rtr1, but not Ssu72, was able to reverse the 6AU sensitivity of set1⌬ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most simply, regions of Ser5 and Ser2 phosphorylation are spatially separated on the CTD, creating thus functional islands. Alternatively, stringent Ser5 dephosphorylation by phosphatases such as Rtr1 or Fcp1 in yeast 43,44 is required in order to render Ser2 phosphorylation possible. A recent study has indeed identified that the human RPAP2 phosphatase specifically recognizes Ser7 phosphorylation marks on the CTD to facilitate Ser5 dephosphorylation 45 .…”
Section: Y S P T S P S Y S P T S P S Y S P T S P Smentioning
confidence: 99%
“…The yeast homologue of RPAP2, Rtr1, has been shown to affect transcription by RNAP II and was identified as an RNAP II specific phophatase that targets the COOH-terminal domain (CTD) of the largest subunit POLR2A/RPB1 during transcription, bringing about a change in the phosphorylation pattern of the CTD that is required for recruitment of termination factors (Gibney et al 2008;Mosley et al 2009). GPN1 is a GTPase that appears to have a role in RNAP II transport from the cytosol to the nucleus (Forget, D., Lacombe, A., and Coulombe, B., unpublished observations).…”
Section: Introductionmentioning
confidence: 99%